2008
DOI: 10.1109/tvcg.2008.109
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Interaction Costs in Information Visualization

Abstract: Interaction cost is an important but poorly understood factor in visualization design. We propose a framework of interaction costs inspired by Norman's Seven Stages of Action to facilitate study. From 484 papers, we collected 61 interaction-related usability problems reported in 32 user studies and placed them into our framework of seven costs: (1) Decision costs to form goals; (2) System-power costs to form system operations; (3) Multiple input mode costs to form physical sequences; (4) Physical-motion costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 53 publications
4
103
0
Order By: Relevance
“…We have specifically analyzed usability problems connected to interaction techniques. As Lam [17] points out, less than a third of a large number of InfoVis papers she surveyed mentioned interaction explicitly. In doing so, we hope to contribute further to the development of a science of interaction [21].…”
Section: Discussionmentioning
confidence: 99%
“…We have specifically analyzed usability problems connected to interaction techniques. As Lam [17] points out, less than a third of a large number of InfoVis papers she surveyed mentioned interaction explicitly. In doing so, we hope to contribute further to the development of a science of interaction [21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on Lam's seven costs [20], we found that both interface tools do not commonly share the three costs such as physical motion cost to execute sequences, visual-cluttering cost to perceive state, and view-change cost to interpret perception. The physical-motion cost is the cost to form physical sequences.…”
Section: Factor Analysismentioning
confidence: 99%
“…ConVis supports multi-faceted exploration of conversations through a set of lightweight interactions (Lam, 2008) that can be easily triggered without causing drastic modifications to the visual encoding. The user can explore interesting topics/ authors by hovering the mouse on them, which highlights the connecting curved links and related comments in the Thread Overview (see Figure 1).…”
Section: Exploring Conversationsmentioning
confidence: 99%